2018
DOI: 10.1007/s10620-018-5199-9
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Rates in Randomized Controlled Trials of Pouchitis Therapy

Abstract: No consistent methods for measuring pouchitis disease activity or defining response and remission were identified, highlighting the need for standardized definitions of outcomes for use in pouchitis trials. Additional high-quality trials are required to evaluate existing and novel therapies in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…Indeed, a recent Cochrane review concluded that only VSL#3-type probiotics were statistically superior to placebos in the prevention or treatment of pouchitis [16,26]. Given the demand for new therapies and lack of evidence for existing treatments, it is of paramount importance that trial design for pouchitis be efficient [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a recent Cochrane review concluded that only VSL#3-type probiotics were statistically superior to placebos in the prevention or treatment of pouchitis [16,26]. Given the demand for new therapies and lack of evidence for existing treatments, it is of paramount importance that trial design for pouchitis be efficient [14].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of pouchitis is largely empirical and only small placebo-controlled trials have been conducted [13,14]. Antibiotics are the main treatment for acute pouchitis, and metronidazole and ciprofloxacin are the most common initial approaches, often resulting in a rapid response, suggesting that dysbiosis is indeed involved in this pathology [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of pouchitis is largely empirical and only small placebo-controlled trials have been conducted [13,14]. Antibiotics are the main treatment for acute pouchitis, and metronidazole and ciprofloxacin are the most common initial approaches, often resulting in a rapid response, suggesting that dysbiosis is indeed involved in this pathology [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are currently very few available data concerning the efficacy of FMT in the prevention of chronic recurrent antibiotic-dependent pouchitis. Moreover, only 15 RCTs have been published on pouchitis with five studies on chronic pouchitis, including only two on maintaining remission, both using probiotic therapies [14]. All the published studies use a variety of different designs and methods of evaluation and scores, and there is currently a need for additional high-quality trials of pouchitis treatments, especially novel therapies.…”
Section: Introductionmentioning
confidence: 99%